Pelatihan Pemanfaatan Sumber Daya Alam Menggunakan Teknik Ecoprint dalam Mendukung Ekonomi Kreatif Desa Beringin Makmur - Irda Sayuti; Adila Ulfa Pulungan; Audi Maia Rachman; Elsa Safitri; Lisa Yuka Ramadhani; Nadila Berliani; Orindu Renjani; Putri Titania Salsabila; Rahmi Yulia Putri; Risa Imanda; Sahnari Tambunan (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
Ecoprint is one of the activities of making batik through the process of transferring color and shape to fabric through direct contact. Ecoprint training was chosen because it was based on the discovery that there were many natural resources that had not been utilized, which was one of the reasons for conducting ecoprint training. In supporting the village's creative economy by utilizing natural resources, ecoprint is one solution that can be implemented. Apart from being able to provide ecoprint training experience, it can be used as an example of a business that supports the village economy. This training uses material delivery and discussion methods, a participatory approach and local potential. The results of this training were to increase the experience and skills of the PKK mothers of Beringin Makmur village regarding ecoprinting. PKK mothers can find out how to make Ecoprint and can apply it at home. Another hope is that mothers can still produce work even though they are stuck at home. Apart from that, the participation method applied not only adds to the learning experience, but also builds a social environment that supports business development. Thus, this activity contributes to community economic empowerment and environmental preservation through creativity and innovation in the use of natural materials found around.